Understanding Vulnerability Patterns of HIV/AIDS among Junior College Male Students: A Knowledge and Attitude Study in Central India - Prashant S Bagdey; Rajan Kumar Barnwal; Vilas V Dudhpachare; Uday W Narlawar (Medsci Publications, 2020)
Introduction: In India, as of 2017 only 32% of young men knew how to prevent HIV (UNAIDS 2018).There is evidence of emerging epidemics among men who have sex with men in areas not previously recognized as having high HIV burdens. There is gap in evidence on knowledge and attitude about HIV/AIDS among male students, particularly from central India. The objective was to assess knowledge & attitude regarding HIV/AIDS among male students of a Junior College. Methodology: This study was conducted in Bramhapuri block of Chandrapur district in Maharashtra. Data was collected from 277 study subjects. Results: Mean Age of participants was 17.31 ± 0.91 years (16 - 25 years). The majority of study subjects 243 (87.73%) had heard about HIV. Knowledge about common mode of HIV/AIDS transmission like unprotected sexual contact, infected needle was found correct in the majority of study subjects. The attitude of study subjects towards person living with HIV (PLWH) was unfavorable with 67.76% subjects agreeing to accept the person in family. The knowledge about HIV/AIDS was better in urban resident students than rural students. Conclusion: Majority of study subjects were aware of HIV/AIDS. However, they lacked complete knowledge about routes of transmission and their attitude towards a PLWH was unfavorable.